W sprawie nowego herbu gminy i miasta Szadek - Adamczewski, Marek (Biuletyn Szadkowski, 2012)
The coat of arms for the town and commune of Szadek was designed and approved in 1990, in accordance with law in force at that time. It was, however, done without consulting heraldists and historians specializing in municipal coats of arms from the period of I Republic of Poland, or persons professionally designing emblems for contemporary municipalities. Consequently, a number of mistakes were made, the most important being that it only partly resembles the town’s heraldic arms from the mid-16th century or the coat of arms from the 17th century, which was incorporated in the altar of Szadek’s parish church to commemorate the citizens who donated funds for its equipment and decoration. According to current quidelines for re-creating coats of arms of urban communes, a municipality should have as its heraldic symbol the historic coat of arms of its capital town or city. Relevant sources indicate that the new emblem of the town and commune of Szadek should contain a city wall with an open gate and three battlemented towers, the exact shape depending on which tradition – 16th or 17th century – is recalled. As regards the heraldic colours, the new coat of arms should have red walls on a golden shield (like that from the 17th century), although a white background is also found for Szadek in publications on heraldic arms of Polish towns and cities.